Performance-Based Legal and Managerial Framework for Minimizing Delay Claims in Urban Construction Megaprojects (Scientific Journal of Research Studies in Future Civil Engineering, 2025)
Urban construction megaprojects are inherently complex, involving multiple stakeholders, extensive capital investment, and intricate regulatory and operational environments. These factors often lead to schedule disruptions and the formation of delay claims, which can significantly increase project costs and jeopardize timely completion. This study proposes a performance-based legal and managerial framework designed to minimize delay claims by integrating clear contractual obligations, quantifiable performance indicators, and proactive managerial controls. The framework emphasizes linking legal responsibilities directly to measurable project outcomes, embedding early-warning mechanisms, and establishing transparent documentation protocols to ensure all stakeholders maintain a shared understanding of expectations and responsibilities. By synthesizing best practices from project management, contract governance, and performance monitoring, the proposed model provides a coherent structure for assessing progress, identifying potential delays, and implementing corrective actions before disputes escalate. The framework is applicable to a wide range of urban megaprojects, including mass transit systems, bridges, mixed-use developments, and large-scale infrastructure corridors. Analysis demonstrates that integrating performance metrics with legal and managerial components improves decision-making, strengthens accountability, and enhances dispute prevention. The study highlights the importance of continuous monitoring, timely interventions, and standardized reporting in mitigating the risk of delay claims. In conclusion, adopting a performance-based governance approach offers a practical and systematic means of reducing disputes, ensuring schedule reliability, and enhancing operational transparency in complex urban construction projects.